دور أبعاد المنظمة المتعلمة في تحسين أداء العاملين دراسة ميدانية في شركتي الاتصال الخلوية (MTN-SYRIATE) في مدينة دمشق - قهوجي أحمد; بدر لما (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدف البحث إلى التعرف على مدى امتلاك شركتي الاتصال الخلوية) MTN-SYRIATE) أبعاد المنظمة المتعلمة، ودور هذه الأبعاد التي حددتها الباحثة بـ (الأسلوب العلمي في حل المشكلات، التعلم المستمر، فرق العمل، التمكين، ذاكرة المنظمة) في تحسين أداء العاملين. ولتحقيق هدف الدراسة تمّ تصميم استبيان لجمع المعلومات من عينة البحث، حيث تكونت العينة من (60) موظف يعملون في شركتي الاتصال الخلوية في مدينة دمشق. و تمّ تحليل البيانات باستخدام البرنامج الإحصائي SPSS. وقد استخدمت الباحثة المنهج لوصفي التحليلي الذي يعتمد على دراسة الظاهرة كما توجد في الواقع. وبعد إجراء عملية التحليل لبيانات الدراسة وفرضياتها، توصلت الدراسة إلى أنّ شركتي الاتصال الخلوية تمتلك أبعاد المنظمة المتعلمة (الأسلوب العلمي في حل المشكلات، التعلم المستمر، فرق العمل، التمكين ذاكرة المنظمة) بدرجة مرتفعة. ووجود علاقة ارتباط ذات دلالة إحصائية بين أبعاد المنظمة المتعلمة وتحسين أداء العاملين. ووجود فروق جوهرية بين آراء المديرين والموظفين حول دور أبعاد المنظمة المتعلمة في تحسين الأداء حيث أعطى المديرون درجة تأييد أعلى من الموظفين. The research aims to identify the extent to which the two cellular communication (MTN-SYRIATE) dimensions of the learning organization, and the role of these dimensions identified by the researcher (b scientific method of problem solving, continuous learning, work teams, empowerment, memory organization) in improving the performance of employees. To achieve the objective of the study questionnaire was designed to collect information from the research sample, where sample consisted of (60) employees working in companies of cellular communication in the city of Damascus. And data were analyzed using the statistical program SPSS. The researcher used the descriptive analytical approach which is based on the study of the phenomenon also exists in reality. After a process of analysis of the study data and assumptions, the study found out that my company owns cellular communication dimensions of the learning organization (the scientific method to solve problems, continuous learning, work teams, enabling the organization’s memory) highly. And the existence of a correlation statistically significant differences between the dimensions of the learning organization and improve the performance of employees. And the existence of significant differences between the views of managers and employees about the role of the dimensions of the learning organization in terms of performance improvement managers gave the highest degree of support staff